COVID-19 y libertad de culto de Chile: la jurisprudencia de la Corte Suprema - Poyanco Bugueño, Rodrigo Andrés (2021)
The pandemic has brought different challenges to the jurisdictional authorities, among them, solving controversies about the health measures adopted by the different Governments. The author focuses on the fundamental right to freedom of worship and how it was affected by the measures adopted by the Chilean Government as a result of COVID-19.  To approach the problem, recent jurisprudence is used, both from the Court of appeals and, mainly, from the Supreme Court of Chile. Through the jurisprudential analysis, the change of position of the Supreme Court is denoted, from a vision according to the restrictive measures dictated by the government, towards a position of defense of the fundamental right to freedom of worship, based both on the Political Constitution of Chile as in international human rights treaties.